Status of diabetes mellitus in different regions of KSA and update on its management - AL-Rasheedi, Mabrouk; Alhazmi, Yasir; AlDaiji, Lamees Abdullah; AlDaiji, Lamya Abdullah; Mobarki, Fatimah Ismail; Almuhaysini, Khuzama Mohammed; Alshammari, Jawza Salem; Almistadi, Nouf Awadh; Yoldash, Saeed Adnan; Almaqwashi, Nouf; Al Abdulgader, Rawabi Saleh; Mashyakhi, Mohammed Yahya; et al. (Frontiers in Clinical Diabetes and Healthcare, 2024)
BackgroundComplications of diabetes and its associated comorbidities can cause rapid progression of type II diabetes mellitus (T2DM). It comes at high costs and affects a patient’s quality of life. We aim to assess T2DM in KSA, including the demographics, medications, complications, and comorbidities, as it remains an integral part of Vision 2030.MethodsObservational retrospective study was designed spanning five administrative regions of KSA. A total of 638 patients’ records were randomly selected from general hospitals and diabetes centers from 2017 to 2020, and the collected were statistically analyzed.ResultsMost (77%) selected patients had uncontrolled diabetes, showing a statistically significant correlation between regions and diabetes control. The Northern, Central, and Southern regions had the highest uncontrolled percentage with less than 20% control, while Western and Eastern regions’ control percentages were around 40% of subjects. Eighty percent of the uncontrolled BP patients had uncontrolled diabetes contrasting the 68% of the BP-controlled patients. Biguanides, DPP-4 inhibitors, GLP-1 agonists, Insulin, and SGLT-2 inhibitors are the most common diabetes medications. Metformin was the most prescribed in all regions, followed by DPP4. Results showed that patients used one to four non-diabetes drugs on average. Dispensing of vitamin B complex and statins were higher in diabetes centers than in hospitals. Retinopathy and peripheral neuropathy were the most common complications, while hypertension and ASCVD were the most common comorbidities.ConclusionResults showed a poor glycemic control situation in the kingdom that necessitates implementing stricter measures to hinder disease progression and reduce complications and comorbidities. Increasing awareness, training, and monitoring programs with larger sample sizes and broader distribution is highly recommended nationally.